Otogenic Pain and Aural Fullness: Mystery Diagnosis. (23rd August 2013) - Micco, Alan G.; Megerian, Cliff; Toh, Elizabeth H.; Angeli, Simon I.
Abstract : Program Description: Otogenic pain and aural fullness can be some of the more frustrating chief complaints to work up and address. Many patients with this complaint are frustrated with a lack of diagnosis and treatment. This leads to multiple visits in search of the answer to their affliction. In this miniseminar, a panel of experts will discuss an appropriate evaluation and workup for these issues. Discussions will highlight appropriate examinations, testing, and imaging, as well as a thorough discussion of the differential diagnoses. Also, recommendations for treatment will be discussed. Case presentations will highlight proper workup and management of these confusing cases. Educational Objectives: 1) Recite likely etiologies of aural fullness and otogenic pain. 2) Recognize potentially serious etiologies of these symptoms. 3) Use appropriate workup and treatment of these symptoms and their causes.